Modern electronic communication - Miller, Gary M. 1941- (Regents/Prentice Hall, 1992)
Provides an introduction to electronic communications while reflecting the rapid changes and improvements taking place in the field. Miller covers topics ranging from electrical noise to digital/data communications, microwaves and fibre optics.